Penerapan Pendekatan Realistik Matematika Edukasi (RME) terhadap Kemampuan Representasi Matematis Siswa Sekolah Dasar - Ramadhani, Ari; Wulandari, Novela; Kusumastuti, Fitri Anisa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Elementary school students’ mathematical representation skills are still rather limited as conventional teaching approaches abound and fall short of appropriately connecting theoretical ideas to actual situations. This study seeks to understand how the Realistic Mathematics Education (RME) strategy influences pupils’ capacity for mathematical representation. Employing A control group for the pretest and posttest strategyThe research method quasiexperimental. Included were two consciously selected fourth-grade classes in Tigaraksa District, Tangerang Regency. The experimental group got RME-based schooling while the control group underwent conventional instruction. The instrument of investigation was a descriptive study evaluating representational abilities in symbolic, visual, and verbal formats. Using SPSS, the data wes then analyzed using homogeneity, normality, matched sample t-test, as well as an independent sample t-test. The study showed an average of 13 points distinction between the posttest and results of the control group and those of the experimental group, indicating a major improvement in pupils’ results. This finding helps the theory that the RME technique can improve students’ ability to represent mathematical concepts a lot. Consequently, at the primary school level, the RME approach has proven to be effective in improving mathematical understanding in a more contextual and significant.Kemampuan representasi matematis siswa sekolah dasar masih tergolong rendah akibat dominasi metode pembelajaran konvensional yang kurang mengaitkan konsep abstrak dengan situasi nyata. Penelitian ini bertujuan untuk mengkaji pengaruh pendekatan Realistik Matematika Edukasi (RME) terhadap peningkatan kemampuan representasi matematis siswa. Dengan menggunakan strategi control group pretest-posttest, metode penelitian ini adalah kuasi eksperimen melibatkan dua kelas IV di Kecamatan Tigaraksa, Kabupaten Tangerang yang dipilih secara purposif. Kelompok eksperimen memperoleh pembelajaran berbasis RME, sedangkan kelompok kontrol mendapat pembelajaran konvensional. Insturmen penelitian berupa tes uraian yang mengukur kemampuan representasi dalam bentuk simbolik, visual, dan verbal, kemudian dianalisis menggunakan uji normalitas, homogenitas, paired sample t-test, dan independent sample t-test dengan bantuan SPSS. Hasil analisis menunjukkan bahwa terdapat peningkatan yang signifikan pada skor posttest siswa di kelas eksperimen dibandingkan dengan kelas kontrol, dengan rata-rata selisih 13 poin. Temuan ini menegaskan bahwa pendekatan RME secara signifikan dapat meningkatkan kemampuan representasi matematis siswa. Dengan demikian, pendekatan RME terbukti efektif mampu meningkatkan pemahaman matematika secara lebih kontekstual dan signifikan.